The Influence of Risk Assessment Instrument Scores on Evaluators’ Risk Opinions and Sexual Offender Containment Recommendations - McCallum, Katherine E. (Criminal justice and behavior, 2017)
In Colorado, evaluators conducting sex offender risk assessments are required to assess 17 risk factors specified by the state’s Sex Offender Management Board (SOMB), in addition to scoring actuarial risk assessment instruments. This study examined the association between instrument scores, the 17 SOMB risk factors, and evaluator opinions concerning risk and need for containment in 302 Colorado cases. Evaluators’ ratings of risk indicated by noninstrument factors were often higher than their ratings of risk indicated by instrument results, but only their ratings of noninstrument factors were independently predictive of containment recommendations. Several of the most influential noninstrument factors (e.g., denial, treatment motivation) have been described by researchers as potentially misleading because they are not predictive of future offending. Findings highlight the need for more studies examining the validity of what risk assessment evaluators actually do, as opposed to what researchers think they should do.